Tales of Research Misconduct: A Lacanian Diagnostics of Integrity Challenges in Science Novels - Zwart, Hub (Library of Ethics and Applied Philosophy, 2017)
research integrity; scientific misconduct; science novels; Lacanian psychoanalysis; continental philosophy; falsification; plagiarism; ethics